A new approach to econometric modeling in digitized consumer behavior - Antohi, Valentin Marian; Zlati, Monica Laura; Ionescu, Romeo Victor; Cristache, Nicoleta (Frontiers in Psychology, 2022)
Given that how to identify motivational factors of online purchasing is critical to the success of online retailers, research on the antecedents of online customer experience (cognitive and affective experiential states) has attracted widespread attention. In this research, we conducted an extensive survey of major discrepancies in the behavior of the buyer of online products according to the age of respondents and synthesized their findings into an econometric model to explain the impact of cultural, social, personal and psychological traits on the online purchasing. Our survey reveals that a myriad of factors have been examined in the context of online buyer's psychological perception in relation to motivational factors and the results on those factors have been reported. The proposed econometric model helps decision makers from online retailers to better understand the motivational factors of online customers, discover recent trends in this stream of research, and shed light on future research.